Psychological characteristics, stressful life events and deliberate self-harm: findings from the Child and Adolescent Self-harm in Europe (CASE) Study. - Madge, N; Hawton, K; McMahon, E; Corcoran, P; De Leo, D; de Wilde, E; Fekete, S; van Heeringen, K; Ystgaard, M; Arensman, E (2011)
There is evidence to suggest that both psychological characteristics and stressful life events are contributory factors in deliberate self-harm among young people. These links, and the possibility of a dose-response relationship between self-harm and both psychological health and life events, were investigated in the context of a seven-country school-based study. Over 30,000, mainly 15 and 16 year olds, completed anonymous questionnaires at secondary schools in Belgium, England, Hungary, Ireland, the Netherlands, Norway and Australia. Pupils were asked to report on thoughts and episodes of self-harm, complete scales on depression and anxiety symptoms, impulsivity and self-esteem and indicate stressful events in their lives. Level and frequency of self-harm was judged according to whether they had thought about harming themselves or reported single or multiple self-harm episodes. Multinomial logistic regression assessed the extent to which psychological characteristics and stressful life events distinguished between adolescents with different self-harm histories. Increased severity of self-harm history was associated with greater depression, anxiety and impulsivity and lower self-esteem and an increased prevalence of all ten life event categories. Female gender, higher impulsivity and experiencing the suicide or self-harm of others, physical or sexual abuse and worries about sexual orientation independently differentiated single-episode self-harmers from adolescents with self-harm thoughts only. Female gender, higher depression, lower self-esteem, experiencing the suicide or self-harm of others, and trouble with the police independently distinguished multiple- from single-episode self-harmers. The findings reinforce the importance of psychological characteristics and stressful life events in adolescent self-harm but nonetheless suggest that some factors are more likely than others to be implicated.